From energy security to security of energy eervices: The role of gendered innovations in living labs - Batinge, B.; Musango, J.K.; Ceschin, F.; Ambole, A.; Smit, S.; Mukama, M.; Petrulaityte, A. (South African Journal of Industrial Engineering, 2022)
Energy security remains a concern in Sub-Saharan Africa. The conceptualisation of energy security at the urban household level has shifted from the security of energy supply to the security of energy services, which is focused more on the demand side. Women and young girls are affected the most by insecure energy services. However, energy policy discourses often fail to focus on the security of energy services or to recognise gender roles in the provision of energy services at the household level. It is therefore imperative to develop innovative and gender-sensitive energy services solutions with a new paradigm of participatory solution design, such as living labs. We assessed living labs and the energy security landscape in poor urban environments through a systematic literature review, and proposed a framework for demonstrating how living labs could be used as a lever to promote the security of energy services. The security of energy services in poor urban households could be improved by harnessing the different innovative strengths of the respective genders. Living labs provide an ideal space for co-generating, co-designing, and co-learning to produce tailored energy services solutions. There is a need for a collaborative effort in resourcing researchers to undertake practical investigations of interactive multi-stakeholder platforms with those who are intended to benefit from the policy to increase its impact and to bridge the science-policy divide. © 2022, South African Institute of Industrial Engineering. All rights reserved.
Keywords: accès à l'électricité; afrique; afrique subsaharienne; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Un projet participatif sur la réduction de la pollution atmosphérique dans quatre pays de l’Afrique de l’Ouest : quel rôle pour les femmes ? - Saint-Charles, Johanne; Yates, Stéphanie; Kêdoté, Nonvignon Marius (Recherches participatives et équité en santé, 2022)
C echapitreportesurlesdéfisd’uneapprocheparticipativeintégrant une perspective d’équité de genre rencontrés dans le cadre d’un programme de recherche-intervention sur la pollution urbaine en Afrique de l’Ouest, programme intitulé « Chaire écosanté sur la pollution urbaine de l’air et les maladies respiratoires1 ». Conçu et dirigé par des chercheurs et chercheuses de quatre pays africains (Bénin, Burkina Faso, Côte d’Ivoire et Sénégal), ce programme regroupait des équipes derecherchedechacundespays(équipes-pays)etquelquescollèguesde«paysdunord»,dontleCanada(Québec).IlaétéfinancéparleCentre de recherches pour le développement international du Canada. Outre des objectifs de recherche et de formation, la Chaire comportait un volet nommé Air-Sain qui visait à sensibiliser les actrices et acteurs dediversmilieuxetàsoutenirdeschangementsdurablesafinderéduirela pollution urbaine.
Keywords: 2000 à aujourd'hui; afrique; afrique de l'ouest; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques

Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Capital, labor, and gender: The consequences of large-scale land transactions on household labor allocation - Hajjar, Reem; Ayana, Alemayehu N.; Rutt, Rebecca; Hinde, Omer; Liao, C.; Keene, Stephanie; Bandiaky-Badji, Solange; Agrawal, Arun (Journal of Peasant Studies, 2020)
Contemporary large-scale land transactions (LSLTs), also called land grabs, are historically unprecedented in their scale and pace. They have provoked robust scholarly debates, yet studies of their gender-differentiated impacts remain more rare, particularly when it comes to how changes in control over land and resources affect women's labor, and thereby their livelihoods and well-being. Our comparative study of four LSLTs in western Ethiopia finds that the transactions led to substantial land use change, including relocation and decrease in size of smallholder parcels, loss of communally-held grazing lands, and loss of forests. These changes had far-reaching impacts on household labor allocation, the gendered division of labor, and household wellbeing. But their effects on women are both more adverse and more severe, expressed in terms of increased wage labor to make up for lost land and livestock, more time spent gathering firewood and water from increasingly distant locations, and an increased intensity of household responsibilities where male members underwent wage labor migration. These burdens led to negative psychological, corporal, and material effects on women living in and near transacted areas compared to their situation prior to transactions. This article both responds to the deficit in studies on the impacts of LSLTs on gendered livelihoods, labor relations, and wellbeing outcomes, and lays the groundwork for future research. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; agriculture; approches et analyses; environnement; inégalités; inégalités hommes-femmes; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; éthiopie

Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis